An econometric analysis of the effectiveness of development finance for the energy sector - Giorgio Gualberti; Luis Filipe Martins; Morgan Bazilian (Fondazione Eni Enrico Mattei (FEEM), 2012)
Reaching the objective of universal access to modern energy services will require large investments in infrastructure in developing countries. An important part of funding will be provided in the form of development finance and its effectiveness in producing positive impacts is crucial for this achievement. This paper presents a panel analysis of the relationship between the installed capacity of electricity generation, the development finance committed for the energy sector, and the gross fixed capital formation. We tested four models with a large dataset and found development finance to have, in most cases, a positive influence on installed base.
Keywords: O19; O21; Q40; 330; International Aid; Energy Access; Aid Effectiveness; Entwicklungsfinanzierung; Elektrizitätsversorgung; Wirkungsanalyse; Entwicklungsländer